The Effect of School Adhocracy Culture on Teacher Effectiveness in Government Aided Secondary Schools in Luwero District, Uganda - Moses, Ddumba; Fredrick, Mugweri (Advances in Social Sciences Research Journal, 2024)
The purpose of the study was to assess the relationship between the school adhocracy culture and teacher effectiveness in government-aided secondary schools in Luwero district of Uganda. The study utilized a mixed survey method with a cross-sectional research design to gather data from a sample population and establish patterns and relationships between school adhocracy culture and teacher effectiveness. This study focused on 645 teachers and 25 Headteachers from government-aided secondary school in Luwero District. Using lists from the schools under study for sampling purposes, teachers were chosen using Krejcie and Morgan’s table approach, with Headteachers of schools chosen as key informants using the purposive sampling technique. The convenience sampling method was employed to select teachers in each school for data collection, ensuring generalization and accessibility to the target population. For data collection, questionnaires, interviewing and observation methods were employed. For descriptive analysis, the teacher skills against the background characteristics were done with the aid of cross-tabulation. Adhocracy culture statements that were scored 100% between the now and the preferred were analyzed with the aid of the ordinary least squares multiple linear regression which was stratified between the coefficients for now and preferred. The analysis of adhocracy factors were found to be associated with lower preferred teacher effectiveness. Overall the study findings revealed that there was no significant relationship between school adhocracy culture and teacher effectiveness. The researcher advises educational institutions to adopt tailored approaches, considering teachers’ demographics and teacher professional development, balance innovation and risk-taking with teacher satisfaction, promote individuality and uniqueness in leadership, optimize resource allocation, and consider fostering a culture of success through initiatives and narratives that support teacher professional growth and student achievement.